Composite microporous membrane, preparation method thereof and battery
By using silicon nitride nanowires and other additives on the microporous membrane of lithium-ion batteries to form an efficient thermal conductivity coating, the problem of poor thermal conductivity improvement in the prior art is solved, and the safety of the battery is significantly improved.
Patent Information
- Application Number
- CN202311065010.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-02-25
AI Technical Summary
While improving the thermal conductivity of the microporous membrane of lithium-ion batteries, the high thermal conductivity of the material is weakened, resulting in the battery's temperature rise too fast during short circuit, which is prone to spontaneous combustion or explosion.
Silicon nitride nanowires are used as the main component of the thermal coating, and by combining them with thickeners, dispersants and adhesives, an efficient thermal coating is formed to improve thermal efficiency.
It significantly improves the thermal conductivity of the battery separator, can quickly conduct heat during short circuit, slow down the increase in the internal temperature of the battery, reduce the risk of spontaneous combustion and explosion, and improve the safety of the battery.
Smart Images

Figure CN119518228A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite microporous membrane and a preparation method thereof, and a battery. Background Art
[0002] Because lithium-ion batteries form lithium crystal trees during use, causing microporous membrane puncture and short circuit, or are impacted by external factors and cause internal short circuit in lithium-ion batteries, the internal short circuit problem of lithium-ion batteries will cause the temperature to rise rapidly. When the temperature reaches a certain level, the lithium-ion battery will spontaneously combust or explode.
[0003] At present, in order to solve the safety problem of short-circuit temperature rise of lithium-ion batteries, the existing technology improves thermal conductivity and reduces the heating rate inside lithium-ion batteries by coating a single or double layer of high thermal conductivity material powder on a PP or PE microporous membrane. However, since the morphology of the currently selected high thermal conductivity coatings is mainly spherical or square, the contact between the powder particles is mostly point contact or point-to-surface contact, and the direct contact between the particles is reduced under the adhesion of the adhesive, so that the high thermal conductivity unique to the material is greatly weakened. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the thermal conductive material in the prior art has a poor effect on improving the thermal conductivity of the microporous membrane, thereby providing a composite microporous membrane and a preparation method thereof, and a battery.
[0005] To this end, the present invention provides the following technical solutions.
[0006] In a first aspect, the present invention provides a composite microporous membrane, comprising a base membrane and a thermally conductive coating disposed on at least one side of the base membrane;
[0007] The thermally conductive coating comprises silicon nitride nanowires;
[0008] The silicon nitride nanowires account for 86-98.5wt% of the mass of the thermal conductive coating;
[0009] The aspect ratio of the silicon nitride nanowire is 50 to 400;
[0010] The length of the silicon nitride nanowire is 20-100 μm.
[0011] Furthermore, the length of the silicon nitride nanowires is preferably 40-80 μm, and further preferably 50-80 μm.
[0012] Furthermore, the aspect ratio of the silicon nitride nanowires is 142-250.
[0013] Furthermore, the thermally conductive coating further comprises a combination of one or more of a thickener, a dispersant and an adhesive.
[0014] Furthermore, the thickener is 0.1-5wt% of the mass of the silicon nitride nanowires, preferably 1-3wt%.
[0015] Furthermore, the dispersant is 0.5-8wt% of the mass of the silicon nitride nanowires, preferably 0.5-2wt%.
[0016] The adhesive is 1-8 wt % of the mass of the silicon nitride nanowires, preferably 2-6 wt %.
[0017] Furthermore, the thickener is a high molecular weight polymer with a weight average molecular weight Mw of 100,000 to 200,000 (ie, 10W to 20W); preferably, it is one or more of sodium carboxymethyl cellulose, carboxymethyl acrylic acid or methacrylic acid.
[0018] Further, the dispersant is one or more of sodium polyacrylate, ammonium polyacrylate, carboxylate or sulfonate;
[0019] Further, the adhesive is a homopolymer or copolymer with a glass transition temperature (Tg) not lower than -10°C; preferably, one or more mixtures or block copolymers of polyacrylate, polyacrylamide, polymethyl methacrylate, polybutyl methacrylate, styrene acrylic latex, polyvinyl acetate, styrene butadiene latex, ethylene-vinyl acetate copolymer, polyvinyl pyrrolidone. Polyacrylate can be polyethyl acrylate, polymethyl acrylate, polybutyl acrylate, polyisooctyl acrylate, etc.
[0020] Furthermore, the base film is made of polyolefin. Exemplarily, the base film is a polyethylene microporous film, a polypropylene microporous film, or a polyolefin multilayer composite microporous film.
[0021] Specifically, the number of layers of the multi-layer composite is more than two layers, and it can be a co-extruded multi-layer or a multi-layer formed by stacking and laminating. Exemplarily, the polyolefin multi-layer composite microporous membrane can be PP / PE / PP, PP / PP / PP, PE / PP / PE.
[0022] Furthermore, the base film has a thickness of 3 to 20 μm;
[0023] Furthermore, the porosity of the basement membrane is 30% to 65%;
[0024] Furthermore, the thickness of the thermal conductive coating is 0.1-5 μm.
[0025] In a second aspect, the present invention provides a method for preparing a composite microporous membrane, comprising the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0026] Furthermore, the silicon nitride nanowires account for 5 to 30 wt %, preferably 10 to 25 wt %, of the total mass of the thermal conductive coating slurry.
[0027] Furthermore, the step of preparing the thermal conductive coating slurry from the silicon nitride nanowires further includes the step of adding at least one of a thickener, a dispersant, an adhesive and a surfactant;
[0028] The surfactant accounts for 0.1-1.5 wt % of the total mass of the thermal conductive coating slurry, preferably 0.1-0.8 wt %.
[0029] Furthermore, the temperature of the drying step is 50-100°C.
[0030] Furthermore, the surfactant is one or more of polyether-modified polysiloxane, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, fatty amine polyoxyethylene ether, fluoroalkyl ethoxy alcohol ether and polyether-modified polysiloxane.
[0031] In a possible design, the step of preparing the silicon nitride nanowires into a thermal conductive coating slurry includes:
[0032] S1, adding the dispersant and silicon nitride nanowires into water, stirring and dispersing, to obtain a mixture a;
[0033] S2. Add the thickener, adhesive and surfactant to the mixture a, stir and disperse them to obtain a thermal conductive coating slurry.
[0034] Furthermore, the thickener is dissolved in water before being added, and the thickener is added to the mixture a in the form of a solution for more uniform dispersion.
[0035] Furthermore, in S1, after adding the dispersant and silicon nitride nanowires, stirring is performed at a speed of 1000 to 4000 rpm for 10 to 60 min; the speed is preferably 1500 to 3000 rpm, and the stirring time is preferably 30 to 50 min.
[0036] Furthermore, in S2, after adding the aqueous solution of the thickener, the adhesive and the surfactant, stirring is performed at a speed of 500-3000 rpm for 10 to 60 min; the speed is preferably 800 to 2000 rpm, and the stirring time is preferably 30 to 50 min.
[0037] Further, in S2, after the stirring is completed, the thermal conductive coating slurry is filtered to remove metal impurities (metal impurities may be introduced into the equipment). Preferably, a 300-mesh filter is used for filtering. Further preferably, the metal iron impurities are removed by an iron remover.
[0038] In a third aspect, the present invention provides a battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the separator comprises the composite microporous membrane or a composite microporous membrane prepared according to the preparation method of the composite microporous membrane.
[0039] The technical solution of the present invention has the following advantages:
[0040] 1. The composite microporous membrane provided by the present invention comprises a base membrane and a thermally conductive coating disposed on at least one side of the base membrane; the thermally conductive coating comprises silicon nitride nanowires; the silicon nitride nanowires account for 86-98.5wt% of the mass of the thermally conductive coating; the aspect ratio of the silicon nitride nanowires is 50-400, and the length of the nanowires is 20-100μm.
[0041] On the one hand, silicon nitride has higher thermal conductivity than the current mainstream alumina and boehmite, and can quickly conduct heat; on the other hand, the microscopic distribution of silicon nitride nanowires in the thermal conductive coating is crisscrossed in a "knitted" shape, which can greatly increase the number of material point-to-surface contacts per unit volume of the thermal conductive coating compared to granular thermal conductive fillers, thereby improving thermal conductivity efficiency. When used in batteries, when the internal temperature rises sharply after a short circuit, the heat can be quickly conducted to the outer shell through the thermal conductive coating, greatly slowing down the process of spontaneous combustion and explosion, and improving battery safety.
[0042] 2. In the composite microporous membrane provided by the present invention, the aspect ratio of silicon nitride nanowires is 142 to 250. Increasing the aspect ratio of silicon nitride nanowires can improve the thermal conductivity coefficient of the thermal conductive coating to a certain extent, because after increasing the aspect ratio, its contact area will also increase to a certain extent; after the aspect ratio of the nanowires increases to a certain extent, the stacking density of the silicon nitride nanowires decreases, resulting in a decrease in the content of silicon nitride nanowires per unit volume of the thermal conductive coating, and the thermal conductivity coefficient of the composite microporous membrane decreases accordingly; on the contrary, if the aspect ratio of the nanowires is reduced, due to the over-dense stacking, the micropore blocking effect on the surface of the base membrane is aggravated, and the permeability increment is increased, resulting in a decrease in the lithium ion pass rate of the composite microporous membrane and an increase in impedance, so the aspect ratio of the silicon nitride nanowires is preferably 142 to 250.
[0043] 3. The thermally conductive coating of the composite microporous membrane of the present invention further comprises a combination of one or more of a thickener, a dispersant and an adhesive; the adhesive is 1 to 8 wt % of the mass of the silicon nitride nanowires.
[0044] The amount of adhesive added is small. By using it in combination with a dispersant, a thickener, and a surfactant, the weakening of the material's unique thermal conductivity caused by the adhesive wrapping is reduced, thereby improving the thermal conductivity of the thermal conductive coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 is a schematic diagram of silicon nitride nanowires in the thermal conductive coating of the composite microporous membrane of Example 1;
[0047] Figure 2 Schematic diagram of granular nano silicon nitride in the thermal conductive coating of the composite microporous membrane of Comparative Example 1. DETAILED DESCRIPTION
[0048] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0049] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0050] The weight average molecular weight of the thickener sodium carboxymethyl cellulose in the embodiments and comparative examples is 12W, the dispersant sodium polyacrylate is manufactured by Baker Gilliney, model number LOPON 885, the adhesive polyethyl acrylate has a glass transition temperature Tg of -3°C, and the surfactant polyether-modified polysiloxane is manufactured by Tego, model number TEGO Wet KL 245.
[0051] Example 1
[0052] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0053] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0054] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0055] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0056] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0057] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0058] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0059] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0060] The balance was deionized water.
[0061] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 142 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0062] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0063] In the composite microporous membrane of this embodiment, the silicon nitride nanowires account for 93.3 wt % of the mass of the thermal conductive coating.
[0064] Example 2
[0065] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0066] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0067] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0068] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0069] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0070] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0071] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0072] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0073] The balance was deionized water.
[0074] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 167 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0075] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0076] Example 3
[0077] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0078] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0079] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0080] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0081] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0082] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0083] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0084] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0085] The balance was deionized water.
[0086] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 200 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0087] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0088] Example 4
[0089] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0090] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0091] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0092] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0093] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0094] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0095] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0096] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0097] The balance was deionized water.
[0098] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 250 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0099] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0100] Example 5
[0101] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0102] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0103] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0104] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0105] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0106] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0107] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0108] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0109] The balance was deionized water.
[0110] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 260 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0111] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0112] Example 6
[0113] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0114] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0115] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0116] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0117] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0118] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0119] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0120] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0121] The balance was deionized water.
[0122] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 278 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane into the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0123] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0124] Example 7
[0125] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0126] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0127] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0128] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0129] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0130] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0131] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0132] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0133] The balance was deionized water.
[0134] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 350 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0135] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0136] Example 8
[0137] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0138] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0139] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0140] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0141] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0142] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0143] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0144] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0145] The balance was deionized water.
[0146] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 400 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0147] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0148] Example 9
[0149] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0150] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0151] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0152] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0153] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0154] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0155] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0156] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0157] The balance was deionized water.
[0158] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 200 and a length of 40 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0159] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0160] Example 10
[0161] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0162] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0163] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0164] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0165] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0166] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0167] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0168] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0169] The balance was deionized water.
[0170] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 200 and a length of 80 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0171] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0172] Embodiment 11
[0173] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0174] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0175] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0176] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0177] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0178] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0179] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0180] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0181] The balance was deionized water.
[0182] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 200 and a length of 100 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0183] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0184] Example 12
[0185] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1.
[0186] The method for preparing the composite microporous membrane of this embodiment includes: the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base membrane, and drying.
[0187] The thermal conductive coating slurry comprises silicon nitride nanowires, a thickener sodium carboxymethyl cellulose, a dispersant sodium polyacrylate, an adhesive polyethyl acrylate, a surfactant polyether modified polysiloxane and deionized water.
[0188] The silicon nitride nanowires are 20wt% of the total mass of the thermal conductive coating slurry;
[0189] Sodium carboxymethyl cellulose is 1.5wt% of the mass of silicon nitride nanowires;
[0190] Sodium polyacrylate is 1.2 wt% of the mass of silicon nitride nanowires;
[0191] The polyethyl acrylate is 3wt% of the mass of the silicon nitride nanowires;
[0192] The polyether-modified polysiloxane is 0.3wt% of the total mass of the thermal conductive coating slurry;
[0193] The balance was deionized water.
[0194] The steps of preparing the thermal conductive coating slurry include: weighing the raw materials according to the above weight content, adding sodium polyacrylate and silicon nitride nanowires with a wire diameter ratio of 125 and a length of 50 μm into deionized water, stirring at 3000 rpm for 40 minutes to form a mixture a; adding sodium carboxymethyl cellulose aqueous solution, polyethyl acrylate and polyether modified polysiloxane to the mixture a, stirring at 1500 rpm for 30 minutes to disperse evenly, and then filtering through a 300-mesh filter, removing metallic iron from the slurry through an iron remover, and obtaining a thermal conductive coating slurry.
[0195] The thermal conductive coating slurry is coated on one side of the base film, the base film is a PE microporous membrane with a porosity of 40%, the thickness of the thermal conductive coating slurry coating is 16 μm, and after being dried in an oven at 70°C, a composite microporous membrane with a single-sided thermal conductive coating thickness of 3 μm is obtained.
[0196] Example 13
[0197] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 3, and the differences are detailed in Table 1.
[0198] Embodiment 14
[0199] This example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 3, except that:
[0200] Sodium carboxymethyl cellulose is 3wt% of the mass of silicon nitride nanowires;
[0201] Sodium polyacrylate is 4wt% of the mass of silicon nitride nanowires;
[0202] The polyethyl acrylate is 5wt% of the mass of the silicon nitride nanowires;
[0203] In the composite microporous membrane of this embodiment, the silicon nitride nanowires account for 88.1 wt % of the mass of the thermal conductive coating.
[0204] Embodiment 15
[0205] This example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 3, except that:
[0206] Sodium carboxymethyl cellulose is 1.0wt% of the mass of silicon nitride nanowires;
[0207] Sodium polyacrylate is 1.5wt% of the mass of silicon nitride nanowires;
[0208] In the composite microporous membrane of this embodiment, the silicon nitride nanowires account for 93.5 wt % of the mass of the thermal conductive coating.
[0209] Comparative Example 1
[0210] This comparative example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 1, except that the silicon nitride nanowires are replaced with bulk nano silicon nitride with a particle size D50 of 800 nm.
[0211] Comparative Example 2
[0212] This comparative example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 1, except that the silicon nitride nanowires are replaced with aluminum oxide with a particle size D50 of 800 nm.
[0213] Comparative Example 3
[0214] This comparative example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 1, except that the silicon nitride nanowires are replaced with blocky nanoboehmite with a particle size D50 of 800 nm.
[0215] Comparative Example 4
[0216] This comparative example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 3, and the differences are shown in Table 1.
[0217] Comparative Example 5
[0218] This comparative example provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 3, and the differences are shown in Table 1.
[0219] Comparative Example 6
[0220] This embodiment provides a composite microporous membrane, and the parameters are shown in Table 1. This comparative example is basically the same as Example 3, and the differences are detailed in Table 1.
[0221] The composite microporous membranes of Examples 1 to 15 and Comparative Examples 1 to 6 were tested, and the results are shown in Table 1.
[0222] Table 1 Composite microporous membrane parameters
[0223]
[0224] The air permeability increment in Table 1 refers to the absolute value of the difference between the air permeability of the base film and the air permeability of the composite microporous film. Air permeability refers to the time it takes for a certain volume of air to pass through a membrane of a specified area under a certain pressure. The air permeability test method refers to GB / T 36363-2018.
[0225] The test method of thermal conductivity coefficient is: using transient plane heat source method thermal conductivity meter (manufacturer: Nanjing Huicheng Instrument Co., Ltd., model: HCDR-S) to measure the thermal conductivity coefficient of the composite microporous membrane.
[0226] From the parameters of Examples 1 to 15 and Comparative Example 1 in Table 1 and Figure 1 and Figure 2 By comparison, it can be seen that compared with bulk nano silicon nitride, the contact area between silicon nitride materials in the microstructure of silicon nitride nanowires is increased, and the thermal conductivity efficiency is improved, so the thermal conductivity coefficient of the thermal conductive coating can be significantly improved.
[0227] From the comparison between Examples 1 to 15 and Comparative Examples 2 and 3, it can be seen that the composite microporous membrane prepared by using silicon nitride nanowires has better thermal conductivity than the composite microporous membranes of nano-alumina and nano-boehmite.
[0228] By comparing Examples 1-15 with Comparative Examples 4-6, it can be seen that the thermal conductivity coefficients of the composite microporous membranes made using silicon nitride nanowires with a length of 20-100 μm and an aspect ratio of 50-400 are all above 5 W / (m·K), and the thermal conductivity is significantly improved.
[0229] It can be seen from Examples 1 to 4, 9 to 11, and 14 to 15 that the thermal conductivity coefficients of the composite microporous membranes made of silicon nitride nanowires with a wire diameter ratio in the range of 142-250 are all above 6 W / (m·K), have better thermal conductivity, and have a good air permeability increment.
[0230] To further illustrate, the base membranes of Examples 1 to 15 can be replaced with PP microporous membranes, PP / PE / PP three-layer co-extruded microporous membranes, or PP / PP / PP three-layer co-extruded microporous membranes to achieve the above-mentioned basically the same effects; the same trend changes mentioned above can also be achieved by having different thicknesses of the thermal conductive coating of the composite microporous membrane.
[0231] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A composite microporous membrane, characterized in that: It includes a base film and a thermal conductive coating disposed on at least one side of the base film; The thermally conductive coating comprises silicon nitride nanowires; The silicon nitride nanowires account for 86-98.5 wt% of the mass of the thermal conductive coating; The aspect ratio of the silicon nitride nanowire is 50 to 400; The length of the silicon nitride nanowire is 20-100 μm.
2. The composite microporous membrane according to claim 1, characterized in that: The aspect ratio of the silicon nitride nanowire is 142-250.
3. The composite microporous membrane according to claim 1, characterized in that: The thermal conductive coating further comprises a combination of one or more of a thickener, a dispersant and an adhesive.
4. The composite microporous membrane according to claim 3, characterized in that: At least one of the following conditions is met: (1) The thickener is 0.1-5wt% of the mass of the silicon nitride nanowires; (2) The dispersant is 0.5 to 8 wt% of the mass of the silicon nitride nanowires; (3) The adhesive is 1 to 8 wt% of the mass of the silicon nitride nanowires.
5. The composite microporous membrane according to claim 4, characterized in that: At least one of the following conditions is met: (1) The thickener is a polymer with a weight average molecular weight Mw of 100,000 to 200,000; (2) The dispersant is one or more of sodium polyacrylate, ammonium polyacrylate, carboxylate or sulfonate; (3) The adhesive is a polymer with a glass transition temperature Tg ≥ -10°C.
6. The composite microporous membrane according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is met: (1) The base film is a polyethylene microporous film, a polypropylene microporous film or a polyolefin multilayer composite microporous film; (2) The base film has a thickness of 3 to 20 μm; (3) The porosity of the basement membrane is 30% to 65%; (4) The thickness of the thermal conductive coating is 0.1 to 5 μm.
7. A method for preparing a composite microporous membrane according to any one of claims 1 to 6, characterized in that: The method comprises the steps of preparing silicon nitride nanowires into a thermal conductive coating slurry, coating the thermal conductive coating slurry on at least one side of a base film, and drying.
8. The method for preparing the composite microporous membrane according to claim 7, characterized in that: The silicon nitride nanowires account for 5 to 30 wt % of the total mass of the thermal conductive coating slurry.
9. The method for preparing a composite microporous membrane according to claim 7 or 8, characterized in that: The step of preparing the thermal conductive coating slurry from the silicon nitride nanowires further comprises the step of adding at least one of a thickener, a dispersant, an adhesive and a surfactant; The surfactant is 0.1-1.5 wt % of the total mass of the thermal conductive coating slurry.
10. A battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The separator comprises the composite microporous membrane according to any one of claims 1 to 6 or a composite microporous membrane prepared according to the method for preparing a composite microporous membrane according to any one of claims 7 to 9.